2012
DOI: 10.3892/ijo.2012.1709
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of metastasis of intravenously-inoculated B16/F10 melanoma cells by the novel ginseng-derived ingredient, gintonin: Involvement of autotaxin inhibition

Abstract: Ginseng has been used for cancer prevention. However, little is known about its active components and the molecular mechanisms underlying its effects. Recently, we isolated a unique lysophosphatidic acid (LPA) receptor ligand, gintonin. Gintonin contains approximately 9.5% LPA, mainly LPA C18:2. Autotaxin (ATX) is responsible for metastasis by overproducing LPA in cancers. However, LPA, particularly LPA C18:2, is a strong negative feedback ATX inhibitor. It is unknown whether gintonin inhibits ATX activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…In this regard, the humanized monoclonal antibody, anti-LPA B3, that targets LPA, is currently under investigation (Crack et al, 2014;Goldshmit et al, 2012). An alternative approach may be to target the enzyme ATX (Gierse et al, 2010;Gupte et al, 2011;Hwang et al, 2013), which contributes to LPA production. There are currently several ATX inhibitors in pre-clinical studies, although none are exclusive for NP.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the humanized monoclonal antibody, anti-LPA B3, that targets LPA, is currently under investigation (Crack et al, 2014;Goldshmit et al, 2012). An alternative approach may be to target the enzyme ATX (Gierse et al, 2010;Gupte et al, 2011;Hwang et al, 2013), which contributes to LPA production. There are currently several ATX inhibitors in pre-clinical studies, although none are exclusive for NP.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…PF-8380 is a specific inhibitor that reduces inflammatory hyperalgesia in rats within 3h (Gierse et al, 2010). Other ATX inhibitors, such as 4PBPA (Gupte et al, 2011), Gintonin (Hwang et al, 2013) and ONO-8430506 (Benesch et al, 2014) are indicated for cancer, although they may also have effects on NP (see Table 1). The first oral therapy developed for MS, i.e.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…7,13) In addition, gintonin inhibits autotaxin activity to suppress metastasis. 8) However, a method for quantifying the amount of gintonin in ginseng has not been developed. In the present study, we produced a monoclonal antibody against gintonin and developed an EIA for gintonin quantitation in ginseng and ginseng products.…”
Section: Detection Of Gintonin In Ginseng Productsmentioning
confidence: 99%
“…2,3,5,6) The gintonin-mediated [Ca 2+ ] i transient is coupled to the regulation of Ca 2,7) Oral administration of gintonin elicits anti-Alzheimer's disease effects in vivo by activating the non-amyloidogenic pathway through LPA receptors and induces anti-metastatic effects by inhibiting autotaxin activity. 7,8) Biochemical analysis has shown that gintonin consists of carbohydrates, lipids, and proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation